Pathways Through Care and After: Unaccompanied minors in England - Jim Wade (Social Work & Society, 2018)
This paper reviews current research evidence on the response of social work services to unaccompanied asylum-seeking young people in England, taking account of recent developments in immigration law and policy. It focuses on the reception and support arrangements that are provided for these young people by local authorities, their experiences of care and the pathways they may take through care towards adulthood. Since most unaccompanied minors (UAM) come to the UK in their mid-teen years, preparation and planning for leaving care should be a central feature of the work undertaken by those social workers, foster parents and residential workers who provide them with support. In this context, evidence is provided on the challenges presented for preparation, planning and aftercare support that arise from the tensions inherent in child welfare and immigration policy and practice. The strategies young people develop to move forward with their life plans, despite continuing uncertainty about their right to residency, are also highlighted. Research on UAM is a relatively new field of enquiry. As such, the need for a sustained program of research, including longitudinal studies that capture young people's experiences into adulthood and their experiences of enforced return is emphasized.